Development of Microcontroller Based GPS Tracking Unit - RIKI NURFALAKHI; SUJONO SUJONO; Tholib Hariono (NEWTON: Networking and Information Technology, 2025)
The development of tracking technology continues to experience innovation with the implementation of various devices and applications. One important component in a tracking system is the effective use of GPS (Global Positioning System) to accurately determine objects' positions. This research aims to design and build a microcontroller-based GPS Tracking unit that can be used as an efficient and economical tracking system. The method used in this development includes hardware design involving a microcontroller as a control center, a GPS module for receiving position data, as well as software development for data integration and processing. The test results show that the designed GPS Tracking unit can track positions with high accuracy and has a fast response time. This system offers a practical and affordable solution for various tracking applications in everyday life as well as in commercial applications. This research contributes to developing tracking technologies that are more independent and easily adapted to specific user needs.